Evaluation of Functional Independence and Pain in Covid-19 Patients with Mild Neurological Impairments during the Hospital Stay - Vijay Krishna Kumar; Archana Puttaiah; Girija Murugan; Shruthi Raju (International Journal of Medical Science and Clinical Research Studies, 2021)
Background: Novel COVID 19 is a infectious disease caused by a recently discovered corona virus. It is characterized as an acute respiratory syndrome followed by neurological diseases like acute necrotizing encephalopathy/disseminated encephalomyelitis, Guillain – barre syndrome, stroke inflammatory neuropathy. Common clinical symptoms include headache, insomnia, dizziness, delirium, myopathy, ataxia, seizures, complete/partial anosmia, ageusia, hypoxia, muscle and nerve pain and peripheral nervous system manifestation. The purpose of this survey was to evaluate the functional independence and pain in Covid-19 patients with mild neurological impairments during the hospital stay. Method: 85 covid–19 diagnosed patients with mild neurological impairments such as non-specific headache, anosmia, aguesia, myalgia, fatigue etc. of age group 25 to 60 years admitted in hospital were recruited. Patient function is assessed using the FIM instrument at the time of admission and at the time of discharge. The severity of the patient’s pain and the impact of this pain on the patient’s daily functioning was evaluated using the brief pain inventory scale. Patients with comorbidity diseases like surgery and cancer, infants, children, ventilated ICU patients were excluded from the study. Results: The study found that among the 85 respondent participants majority of 53(62.4%) had severe pain and 82 of them(96.5%) had high pain interference. According to the interpretation the total FIM score shows a significant improvement from admission to discharge with the p-value of 0.000. Conclusion: The study concluded that there was a significant difference on functional independence and pain in Covid-19 patients with mild neurological impairments during the hospital stay.